Effect of wind directions on human injury and fatality risk modeling due to vapor cloud explosion in offshore platforms - Niazi, U.M. (John Wiley and Sons Inc., 2020)
Vapor cloud explosion (VCE) accidents have the potential to cause loss of life in offshore platforms. In order to quantify risk, quantitative risk assessment has served as a robust methodology. However, previous research focuses on macroscale assessment of risk which does not take into consideration the local specific details such as piping and equipment congestions. The overpressure developed by VCE is greatly influenced by local specific details. In addition, VCE occurs due to the ignition of vapor cloud that is influenced by parameters such as wind speeds and directions. This study investigates the effect of different wind conditions on VCE and resulting human injury and fatality risk by employing a grid-based approach in an offshore platform. Flame Acceleration Simulator software is utilized to model dispersion of vapor cloud and resulting VCE. The methodology is an integrated tool that enables a grid-by-grid mapping risk, thereby providing a complete and precise picture of risk in all the locations. It was found that risk values were increased to maximum of 91 when wind speed was increased from 0 to 7 m/s. Among four wind directions, West to East wind direction recorded maximum risk values and South to North wind direction recorded minimum risk values. Â© 2019 American Institute of Chemical Engineers